2021
DOI: 10.3390/ijms222111880
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of the Metabolome and Transcriptome on Anthocyanin Biosynthesis in Four Developmental Stages of Cerasus humilis Peel Coloration

Abstract: Cerasus humilis is a unique dwarf shrub and fruit color is an important trait in the species. In this study, we evaluated the transcriptomic and metabolomic profiles of the plant at different developmental stages to elucidate the mechanism underlying color formation. In a metabolomics analysis, 16 anthocyanin components were identified at four developmental stages, and high levels of cyanidin O-syringic acid and pelargonidin 3-O-beta-d-glucoside (callitephin chloride) were correlated with the reddening of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…The total number of metabolites in plants is as high as 200,000, making them an ideal target for studying biosynthesis regulation [ 68 ]. In recent years, the genetic mechanism of plant metabolite changes has been studied [ 69 , 70 ]. We detected 650 metabolites that could be annotated in MS2 database using the extensive targeted metabolomics method, and the number of detected metabolites was higher than that of previous studies on frost resistance of wheat [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The total number of metabolites in plants is as high as 200,000, making them an ideal target for studying biosynthesis regulation [ 68 ]. In recent years, the genetic mechanism of plant metabolite changes has been studied [ 69 , 70 ]. We detected 650 metabolites that could be annotated in MS2 database using the extensive targeted metabolomics method, and the number of detected metabolites was higher than that of previous studies on frost resistance of wheat [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sok . [ 33 ]. Therefore, these results proposed that the difference between red fruit and yellow fruit in N. tangutorum was mainly due to the process catalyzed by UFGT, in another word, stable anthocyanin glycosides cannot be formed in JC so that the yellow fruit of JC fails to show red coloration.…”
Section: Discussionmentioning
confidence: 99%
“…Existing experimental evidence supports that anthocyanins and their metabolites are favorable to alleviating atherosclerosis ( 22 ), which is characterized by the occurrence of lipid deposition in medium-large arterial walls mainly resulting from dysfunction in lipid metabolism and chronic inflammation. Recently, studies on anthocyanins of cherries and their related products have been increasing for exploring the color formation and health benefits via multiple omics technologies such as metabolomics and transcriptomics ( 16 ). Nevertheless, results from some anthocyanins-dietary intervention experiments on animal models and human subjects are not consistent.…”
Section: Discussionmentioning
confidence: 99%
“…It has become a powerful tool for discovering potential biomarkers and exploring molecular mechanisms underlying diseases, with widespread application to nutrition and health ( 15 ). It has been reported that integrating analysis of metabolome and transcriptome was employed to reveal the association between color changes and anthocyanins ( 16 ). Recently, Chen et al ( 17 ) investigated the effects of anthocyanin extracts from bilberry and purple potato on the plasma metabolomic profile of Zucker diabetic fatty rats.…”
Section: Introductionmentioning
confidence: 99%